2022
DOI: 10.2903/j.efsa.2022.7291
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the proposed amendment of the specifications for enzymatically produced steviol glycosides (E 960c): Rebaudioside D produced via enzymatic bioconversion of purified stevia leaf extract

Abstract: The EFSA Panel on Food Additives and Flavourings (FAF Panel) provides a scientific opinion on the safety of a proposed amendment of the specifications of enzymatically produced steviol glycosides (E 960c) with respect to the inclusion of rebaudioside D produced via enzyme‐catalysed bioconversion of purified stevia leaf extract. Rebaudioside D (95% on dry basis) is produced via enzymatic bioconversion of purified stevia leaf extract using uridine diphosphate (UDP)‐glucosyltransferase (UGT) and sucrose synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The authors concluded that the metabolism of the test item indicated a rapid deglycosylation to a final steviol metabolite. These results are consistent with those previously considered in other scientific opinions of the Panel (EFSA FAF Panel, 2019, 2022.…”
Section: Other Studiessupporting
confidence: 93%
See 4 more Smart Citations
“…The authors concluded that the metabolism of the test item indicated a rapid deglycosylation to a final steviol metabolite. These results are consistent with those previously considered in other scientific opinions of the Panel (EFSA FAF Panel, 2019, 2022.…”
Section: Other Studiessupporting
confidence: 93%
“…The Panel considered that the metabolic fate of steviol glycosides, including steviol glycosides obtained via fermentation, leads to the aglycone which is absorbed. Given that all steviol glycosides follow the same metabolic pathways, the Panel considered that the current steviol glycosides would fall within the same group of substances (EFSA ANS Panel, 2010 ; EFSA FAF Panel, 2020 , 2022 ), and the group approach would be applicable. Therefore, the Panel considered that the already existing data on rebaudioside M and structural‐related steviol glycosides (EFSA ANS Panel, 2010 ; EFSA FAF Panel, 2019 , 2020 , 2021 , 2022 ), along with new supportive toxicity data on rebaudioside A produced fermentatively by Y. lipolytica (same manufacturing process of the proposed food additive), are sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations